PETROGENESIS OF DACITE IN AN OCEANIC SUBDUCTION ENVIRONMENT: RAOUL ISLAND, KERMADEC ARC - Smith I.E.M.; Worthington T.J.; Price R.C.; Stewart R.B.; Maas R. (My University, 2006)
Raoul Volcano in the northern Kermadec arc is typical of volcanoes in oceanic subduction systems in that it is composed mainly of low-K high-Al basalts and basaltic andesite. However, during the last 4 ka Raoul Volcano has produced mainly dacite magma in pyroclastic eruptions associated with caldera formation. The rocks produced in these episodes are almost aphyric containing only sparse crystals of plagioclase, clinopyroxene, orthopyroxene and magnetite. These apparent phenocrysts have chemical compositions that suggest that they did not crystallise from melts with the chemical composition of their host rocks. Rather they are xenocrysts and only their rims show evidence for crystallisation from their host melt. Chemical compositions of samples of the dacites show that each eruption has tapped a distinct magma batch. Compositional variations through the analysed suite cannot be accommodated in any reasonable model of fractional crystallisation from likely parental magma compositions. The hypothesis that best fits the petrology of Raoul Island dacites is one of crustal anatexis. This model requires heating of the lower crust by a magma flux to the point where dehydration melting associated with amphibole breakdown produces magma from a preconditioned source. It is suggested that Raoul is passing through an adolescent stage of development in which siliceous melts are part of an open system in which felsic and mafic magmas coexist. © 2006 Elsevier B.V. All rights reserved.
Keywords: CRUSTAL ANATEXIS; DACITE; FRACTIONAL CRYSTALLISATION; KERMADEC ARC; OCEANIC SUBDUCTION